Controlled‐Release Fertilizer Effect on Potato and Groundwater Nitrogen in Sandy Soil. (1st March 2014) - Bero, Nicholas J.; Ruark, Matthew D.; Lowery, Birl
Abstract : Controlled‐release fertilizer, specifically polymer coated urea (PCU), may reduce nitrate‐nitrogen (NO3 –N) leaching to ground water; however, few if any field scale studies have been performed in Wisconsin on sandy soils to validate these assertions. A 2‐yr field experiment was conducted at the Hancock Agricultural Research Station using potato ( Solanum tuberosum L.) planted in Plainfield sand. Experimental design was a randomized complete block with three replicates and four N fertilizer treatments: (i) no N, (ii) 224 kg N ha −1 as PCU, (iii) 280 kg N ha −1 as PCU, and (iv) 280 kg N ha −1 split‐applied as ammonium sulfate [(NH4 )2 SO4 ] and ammonium nitrate (NH4 NO3 ) fertilizer. Three groundwater monitoring wells were installed in each plot, sampled weekly during the growing season, and analyzed for NO3 –N, ammonium (NH4 –N), and dissolved organic N. Potato N uptake and yields were similar among conventional fertilizer and the PCU treatments; PCU may only be economically viable when applied at lower than recommended rates. Significant increases in the partial nutrient balance (PNB) were calculated for 224 kg N ha −1 of PCU compared to 280 kg ha −1 of PCU or conventional fertilizer. These large gains in N use efficiency were not reflected in the groundwater quality. The plot‐to‐plot variation in groundwater nitrate concentration was too large to statistically determine differences among fertilizer treatments. Therefore, relying on measurements of N uptake and N use efficiency are the clearest way to assess impacts of N fertilizer on groundwater quality.